Effects of UV Irradation on Electrospun PLLA and PAN in the Production of Short Electropun Fibres Using Ultrasonication Method - Marini, Sawawi (UPM Press, 2023)
This work showed that exposure of ductile electrospun polymers, namely poly-L-Lactide acid (PLLA) and polyacrylonitrile (PAN) to UV-Ozone, leads to the embrittlement of fibres. Young’s modulus for PLLA and PAN increased by 39% and 78%, respectively. Meanwhile, the ductility was reduced by 23% for PLLA and 40% for PAN. The SEM images show that the UV irradiation resulted in a surface pitted of PLLA and no changes in PAN surface morphology. The ATR-FTIR results indicate that this treatment did not change the chemical structure of the electrospun PLLA and PAN fibres. The as-spun polymers that failed to be scission directly using ultrasonication can now be fragmented into micron-length short fibres after the UV irradiation treatment. The minimum time to produce the short fibres is 18 mins for PAN and 29 mins for PLLA. It indicates ultrasonication is suitable for producing short electrospun fibres, even for ductile materials.